Cover Picture: Adjacent Lone Pair (ALP) Effect: A Computational Approach for Its Origin (Chem. Eur. J. 22/2016). Issue 22 (26th April 2016) - Zhang, Huaiyu; Wu, Wei; Ahmed, Basil M.; Mezei, Gellert; Mo, Yirong
Abstract : 1‐Substituted pyrazole can be deprotonated either at its 3‐ or 5‐position, but the 5‐position is overwhelmingly preferred as the resulting anion is more stable than the deprotonated anion at the 3‐position by both enhanced π conjugation and nucleus–electron electrostatic attraction. Thus, the nature of the renowned adjacent lone pair (ALP) effect is not the generally believed Pauli exchange repulsion between the lone pairs. More information can be found in the Full Paper by W. Wu, Y. Mo et al. on page 7415 ff.